First measurement of the $$C\!P$$ C P -violating phase in $${{B} ^0_{s}} \!\rightarrow {{J /\psi }} ($$ B s 0 → J / ψ ( $$\rightarrow $$ → $$e ^+e ^-$$ e + e - ) $$\phi $$ ϕ decays - LHCb Collaboration (SpringerOpen, 2021)
Abstract A flavour-tagged time-dependent angular analysis of $${{B} ^0_{s}} \!\rightarrow {{J /\psi }} \phi $$ B s 0 → J / ψ ϕ decays is presented where the $${J /\psi }$$ J / ψ meson is reconstructed through its decay to an $$e ^+e ^-$$ e + e - pair. The analysis uses a sample of pp collision data recorded with the LHCb experiment at centre-of-mass energies of 7 and $$8\text {\,Te V} $$ 8 \,Te V , corresponding to an integrated luminosity of $$3 \text {\,fb} ^{-1} $$ 3 \,fb - 1 . The $$C\!P$$ C P -violating phase and lifetime parameters of the $${B} ^0_{s} $$ B s 0 system are measured to be $${\phi _{{s}}} =0.00\pm 0.28\pm 0.07\text {\,rad}$$ ϕ s = 0.00 ± 0.28 ± 0.07 \,rad , $${\Delta \Gamma _{{s}}} =0.115\pm 0.045\pm 0.011\text {\,ps} ^{-1} $$ Δ Γ s = 0.115 ± 0.045 ± 0.011 \,ps - 1 and $${\Gamma _{{s}}} =0.608\pm 0.018\pm 0.012\text {\,ps} ^{-1} $$ Γ s = 0.608 ± 0.018 ± 0.012 \,ps - 1 where the first uncertainty is statistical and the second systematic. This is the first time that $$C\!P$$ C P -violating parameters are measured in the $${{B} ^0_{s}} \!\rightarrow {{J /\psi }} \phi $$ B s 0 → J / ψ ϕ decay with an $$e ^+e ^-$$ e + e - pair in the final state. The results are consistent with previous measurements in other channels and with the Standard Model predictions.